CHANGES IN THE HEALTHCARE SECTOR IN NEW UZBEKISTAN (THE CASE OF SURKHANDARYA REGION) (World Bulletin of Social Sciences, 2026)
This article highlights the progress of reforms in the healthcare sector in recent years in our country, particularly in the Surkhandarya region. It examines the changes in the material and technical base of medical institutions in the region and the transition of the regional healthcare system to a new model.
Keywords: Healthcare system; medical sector; private clinics; material and technical base